Secondary processing in biscuit manufacturing. Manual 5 : chocolate enrobing, moulding, sandwich creaming, icing, application of jam, marshmallow, caramel, troubleshooting tips - Manley, Duncan (Woodhead Publishing, 1998)
This manual takes readers through such secondary processes as coating, sandwiching and icing, concentrating on common production problems and how they can be solved.
"Biscuit, cookie and cracker manufacturing manuals"--Cover
Keywords: Cookies -- Laboratory manuals.; elektronické knihy; electronic books